Pengaruh Pendidikan Kewirausahaan Terhadap Minat dan Kreatifitas Berwirausaha Mahasiswa Tadris IPS UIN Sayyid Ali Rahmatullah Tulungagung - Nadya Khusna Alfiany; Dita Hendriani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This research departs from the large number of tuition in Indonesia and the lack of entrepreneurs who graduated from universities. This study aims to find out: 1) Is there an influence of entrepreneurship education on the entrepreneurial interest of Tadris IPS students of UIN Sayyid Ali Rahmatullah Tulungagung? 2) Is there an influence of entrepreneurship education on the creativity of Tadris IPS students of UIN Sayyid Ali Rahmatullah Tulungagung? The benefit of this research is to provide an understanding of the influence of entrepreneurship education on students and related institutions in the hope of motivating and increasing students' interest and creativity in entrepreneurship. This study uses a quantitative approach because the data of this research is in the form of numbers that have gone through statistical analysis. This study uses numbers to explain and describe the results that have been tested with real life. Based on the results of the determination coefficient test (R Square), entrepreneurship education has an influence of 21.2% on students' interest in entrepreneurship. Based on the results of the determination coefficient test (R Square), entrepreneurship education has an influence of 5.7%. This means that entrepreneurship education only explains 5.7% of the variation in entrepreneurial creativity, so there are still other external factors that are more dominant in influencing students' interest and creativity. The results of this study indicate that entrepreneurship education plays an important role in increasing students' interest and creativity in entrepreneurship. Therefore, improving the quality of entrepreneurship education and adding practical experience can further encourage student creativity in entrepreneurship. This also shows the need for additional support for other factors that affect creativity so that entrepreneurship education can be more optimal in encouraging business innovation among students.